RADIATION - Bansal, Shivam; Vashiath, Yogesh; Batra, Ujjwal (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Radiation is energy that comes from a source and travels through some material or through space. Light, heat and sound are types of radiation. The kind of radiation discussed in this presentation is called ionizing radiation because it can produce charged particles (ions) in matter. Ionizing radiation is produced by unstable atoms. Unstable atoms differ from stable atoms because they have an excess of energy or mass or both. Unstable atoms are said to be radioactive. In order to reach stability, these atoms give off, or emit, the excess energy or mass. These emissions are called radiation. The kinds of radiation are electromagnetic (like light) and particulate (i.e., mass given off with the energy of motion). Gamma radiation and X-rays are examples of electromagnetic radiation. Beta and alpha radiation are examples of particulate radiation. Ionizing radiation can also be produced by devices such as X-ray machines. Radiation is the emission or transmission of energy in the form of waves or particles through space or through a material medium.[1][2] This includes electro-magnetic radiation such as radio waves,visible light, and xrays, particle radiation such as α, β, and neutron radiation and acoustic radiation such as ultrasound, sound, and seismic waves. Radiation may also refer to the energy, waves, or particles being radiated.